Pengungkapan Risiko Keuangan Perbankan Dilihat dari Corporate Governance - Sholikhah, Himmatus; Sari, Shinta Permata (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
Banking sector is one of economics sectors that support the rapid improvement on economic growth, but the economic instability make banking companies inseparable from financial risk. In order to maintain business continuity, banking companies must carry out good corporate governance to represent financial risk disclosure as a priority preview for stakeholders. This study analyze the effect of corporate governance proxies by proportion of the independent commissioners, expertise of audit committee, ownership concentration, and auditor's reputation on financial risk disclosure. The purposive sampling methods use to classify the banking companies listed on the Indonesia Stock Exchange in 2016-2018 which consist of 42 banks. The multiple linear regression uses to analyze the data and the results indicate that auditor’s reputation effects on financial risk disclosure. Meanwhile, proportion of the independent commissioners, expertise of audit committee and ownership concentration have no effect on financial risk disclosure.